You can take a horse to water ...environmental education theory and practice in the context of a simple freshwater ecology exercise - Alistair Clacherty (Environmental Association of Southern Africa, 1989)
This article deals with some important considerations which should be taken into account in the planning and execution of environmental education activities. It questions the educational benefits of teaching and learning that rely on the transmission of information, and explores an alternative epistemological basis for such work. It suggests that a discussion-based approach focused on experiences of actual environmental issues, encountered problematically, should characterise environmental education activities. A simple ecology exercise dealing with organic pollution of a river is provided as a context for the educational principles and ecological concepts which are described.